Optimization of the culture medium composition using response surface methodology for new recombinant cyprosin B production in bioreactor for cheese production - Sampaio, Pedro (2020)
The optimization of culture medium composition was carried out for improvement the recombinant cyprosin B production, an enzyme with high milk-clotting activity. Response surface methodology (RSM) was applied to evaluate the effect of variables namely glucose, yeast extract (YE) and bactopeptone present in the culture medium, used for recombinant cyprosin B production by transformed Saccharomyces cerevisiae BJ1991 strain in shake-flask and bioreactor culture conditions. The central composite experimental design (CCD) was adopted to derive a statistical model for optimizing the composition of the fermentation medium. The optimal concentration estimated for each variable related to a theoretical maximum of cyprosin B activity (488 U mL-1 ) was 30 g L-1 glucose, 15 g L-1 YE and 27 g L-1 bactopeptone. The optimized medium composition, based on empirical model, led to a cyprosin B activity of 519 U mL-1 , which corresponds to an increase of 46%. The fermentation using optimized culture medium in a 5-L bioreactor allowed a significant increase in biomass (82%) and recombinant cyprosin B production (139%). The improvement in the recombinant cyprosin B production after optimization process can be considered adequate for large-scale applications, and the clotting activity of cyprosin B account for their use in industrial cheese making.